Damage states of nine-story tunnel form building under earthquake excitations using Ruaumoko 2D program - A. Karimi, N.; H. Hamid, N.; Karimi, N. (International Journal of Engineering and Technology, 2019)
A lot of structural damage was observed after the earthquakes and it is very important to determine the level of safety of these buildings. One of the popular construction methods in Malaysia is a tunnel form building system which built for apartments, condominiums and residential houses using British Standard known as BS 8110. This standard is the non-seismic code of practice. Subsequently, a prototype four bay nine-story tunnel form building system was designed using STAAD PRO program and modeling using Ruaumoko 2D program under seven past ground motion records. The nonlinear time history analysis and parameters of dynamic analysis were obtained from this program. The earthquake excitations, spectral displacements, pseudo spectral accelerations, mode shapes and maximum deformations were used to determine the level of safety for this type of building. The comparison was made between the experimental results and Â modeling results in order to assess the levels of safety for seven past ground motions. It can be concluded that this building survives under Bukit Tinggi Earthquake and Greece Earthquake, severe damage under EL-Centro North South Earthquake and Pacoima Dam Earthquake and collapse under the 1940EL-Centro East West Earthquake, Norway Earthquake and the 1985 Mexico City Earthquake.Â Â